EFFECT OF PRODUCTION COSTS, PROMOTIONAL COSTS, AND SALES VOLUME ON NET PROFIT IN MANUFACTURING COMPANIES - Naftalia Padang; Suwar Irnihsyah Irawan; Rifani Atika; Jenny Br.Manalu; Jessy Safitri Sitorus (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The purpose of this research is to find out whether there is an influence between the variables of sales volume, promotional costs, and production costs on net income in food and beverage sub-sector manufacturing companies that have been registered on the IDX for the 2016-2019 period. This research was carried out using a quantitative approach. The annual financial report data used comes from the website www.idx.co.id. The population used for this is 26 companies and the total sample is 44 companies. This study shows the results that, partially production costs do not have a significant effect on net income, partial promotion costs do not have a significant effect on net income, sales volume partially has a significant effect on net income, sales volume, production costs , promotion costs simultaneously have a significant effect on net profit in food and beverage sub-sector manufacturing companies that have been registered on the IDX for the 2016-2019 period. The coefficient of determination is 0.888, which means that the influence of production costs, promotion costs, and sales volume on net income variable is 88.8%. Having a remaining 11.2% is caused by variables outside of this study